2014
DOI: 10.1103/physrevb.89.201407
|View full text |Cite
|
Sign up to set email alerts
|

Casimir quantum levitation tuned by means of material properties and geometries

Abstract: The Casimir force between two surfaces is attractive in most cases. Although stable suspension of nano-objects has been achieved, the sophisticated geometries make them difficult to be merged with well-established thin film processes. We find that by introducing thin film surface coating on porous substrates, a repulsive to attractive force transition is achieved when the separations are increased in planar geometries, resulting in a stable suspension of two surfaces near the force transition separation. Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 23 publications
2
25
0
Order By: Relevance
“…We can still infer that by inducing more pores, a transition from desorption to adsorption of bubbles is predicted near a porous SiO 2 in water. This is in line with the work of Lifshitz et al and others [3][4][5][6][7][8], which predicts changes in attraction to repulsion depending on the dielectric functions in the three-layer system. Gas bubbles that could include CO 2 molecules may bind by physisorption to a porous SiO 2 surface.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…We can still infer that by inducing more pores, a transition from desorption to adsorption of bubbles is predicted near a porous SiO 2 in water. This is in line with the work of Lifshitz et al and others [3][4][5][6][7][8], which predicts changes in attraction to repulsion depending on the dielectric functions in the three-layer system. Gas bubbles that could include CO 2 molecules may bind by physisorption to a porous SiO 2 surface.…”
Section: Introductionsupporting
confidence: 92%
“…A well-known aspect of the Casimir-Lifshitz force is that, according to theory, it can also be repulsive [3][4][5][6]. It has been speculated that this effect could allow quantum levitation of nanoscale devices [6][7][8]. It was demonstrated by Phan and Viet [9], and by Boström et al [10], that the force may change sign as the separation is increased.…”
Section: Introductionmentioning
confidence: 99%
“…We observe that the dielectric function of water [1], ice [1], silica [14] and gold [37] can be found as parameterised dielectric functions in the literature. Together with the Lifshitz theory in multilayer systems, described in many papers ( see for instance previous works [6,31,32,[46][47][48]), this makes our main results straightforward to reproduce. The dielectric functions for ice and water have in the past also been used in a study as approximate dielectric functions for water in different phases, at other temperatures and pressures, in a study of van der Waals (vdW) interactions involving methane gas hydrates (i.e.…”
mentioning
confidence: 75%
“…The details for calculations of this kind of geometries were outlined recently by Dou et al. [6,32] The Lifshitz pressure is given by the negative of the derivative of the Lifshitz energy with respect to the water film thickness. In the present work, we cal- [14].…”
mentioning
confidence: 99%
“…Very recently in Ref. [164] the authors suggested controlled quantum Casimir levitation caused by the introduction of thin film surface coating on a porous planar substrates both immersed in a suitable fluid. More specifically, they have shown that the Casimir force between Teflon and cassiterite (SnO 2 ) nanosheet immersed in cyclodecane is attractive at large separations but repulsive at small separations, resulting in a stable equilibrium distance where the total force is zero.…”
Section: Experimental Feasibility Of the Predicted Effectmentioning
confidence: 99%